আমার বিক্রমপুর - বাড়রী, হরিআনন্দ ১৯২৯- (কলকাতা : আনন্দ, 2006)
Articles chiefly on the cultural history of Munshiganj District, Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English and Sanskrit
Keywords: Munshiganj District (Bangladesh) -- Civilization